Pemekaran Negeri Kata-kata: Konfigurasi Kebudayaan Melayu di Riau - Jan van der Putten (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2006)
Since a long time ago artists in Riau Province have been proud with their contributon to the estabilishment of Indonesia as a nation-state in the form of language. Language is perceived not onlu as a means of communication in order to convey messages in a direct manner, but also as a complex civilization that includes manner, behavior, and way of life. Therefore, language does not ‘merely’ serve as an instrument, as it also refers to the overall complexity of life and is considered to be one of the determining factors that shape one’s identity.Unfortunately, ever since the handover of that contribution to the nation-state Indonesia, the contributors are no longer in the position to control and dierect the future development. In other words, the contributed a language, but the development of that language afterwards as the national language of modern state is no longer managed and monitored by them, but rather, by foreigners such as the Dutch, or other ethnic groups such as the Minangkabau through Balai Pustaka and the Javanese through the dominant discourse of the state. This has made the Malay language that exists in Riau a local language whose speakers are smaller comparaed to those of other local languages.It is not surprising, therefore, that many artists become disappointed and upset with the way ‘their’ language is developed by the center, i.e., Java/Jakarta. After the Reformasi and the ratification of the Regional Autonomy Bill, some developments have been taking palce, which is quite promising for those situated in the periphery as they will be able to play a new role in the ethnic configuration of the country. This article looks into the new development occurig in Riau after the Reformasi, as the implementation of regional autonomy and expansion has brought about the birth of two new provinces, i.e., Riau (inland) with Pekanbaru as its capital and Riau Islands with Tanjung Pinang as its administrative center. The latter is a new province which consist of several new regencies. In such a development, it is interesting to examine how these administrative regions develop their cultural uniqueness and how the linguistic ‘trauma’ that haunts the artists might be either overcome or worsen by the recent development.